Estetika Kassian Cephas, Fotografer Jawa yang Mendunia - Pamungkas Wahyu Setiyanto (Rekam: Jurnal Fotografi, Televisi, Animasi)
Looking at a photo means a provement to past time’s existence. Aphoto is similar with an arrow which is ready to be launched from the pasttime to present’s era. Hence, through a photo we do have an experience acronological time. Whereas a photo becomes a mediation to experience thepast time and to experience a cronological flow which is relate the past andthe present time. With that understanding I want to talk about the past time’sphotographer. He is a Javanese who is able to bring and to introduce themodernity that time to the citizen through himself and his works in photoforms. He is Kassian Cephas, the first Javanese who knew a camera. Thus, heis known as the father of Indonesia’s photography.